Numerical analysis of beam steering for Si-photonics-LiDAR - Chen, Yiru (Nanyang Technological University, 2023)
Silicon-based optical phased array LIDAR is a new type of LIDAR technology that enables height control and adjustment of the beam to achieve high precision ranging and imaging. This technology has a wide application potential in modern autonomous driving, robot navigation, and UAV obstacle avoidance. The silicon-based optical phased array LIDAR has higher reliability, higher angular resolution and a smaller size than the traditional mechanical scanning LIDAR, which can achieve more efficient obstacle detection and path planning, and it is expected to accelerate the development of autonomous driving technology. Literature shows that in general, optical phased arrays can achieve beam steering of a few degrees to 20 degrees. This thesis presents the design and simulation of a silicon-based optical phased array capable of beam steering over a range of angles. The design process began with determining the appropri ate grating coupler size, and the waveguide spacing was verified using FDTD simulation to optimize the transmitting efficiency while minimizing unnecessary side flaps and mutual coupling between antennas. The parameters of a single antenna were confirmed, and the antenna spacing and weights were further op timized using MATLAB to match the desired pattern. A compact model was then created using INTERCONNECT, and the angular data from the phased ar ray simulation was imported into the model to observe the change of angle over time. The results demonstrate that the phased array is capable of achieving a longitudinal θ angle rotation of approximately 24 degrees and a beam width of approximately 3 degrees.